Comparative evaluation of encapsulation using β‐cyclodextrin versus freeze‐drying for better retention and stabilizing of black Périgord truffle (Tuber melanosporum) aroma. Issue 8 (5th July 2022) - Phong, Win Nee; Al‐Salami, Hani; Gibberd, Mark R.; Dykes, Gary A.; Payne, Alan D.; Coorey, Ranil
Abstract : Abstract: This study aimed to develop a novel technique to retain and stabilize compounds contributing to truffle aroma by encapsulation using β‐cyclodextrin. Two experiments were conducted. In the first experiment, the key volatile profile and microbial population of products resulting from three different encapsulation methods, namely direct mixing method (M1), direct mixing followed by ethanol addition method (M2), and paste method (M3), were compared with untreated truffles (positive control) over a 90‐day period. The M2‐derived product was the least optimal for retaining key volatile compounds despite showing the lowest microbial population. There was no significant difference in the volatile profile of products derived from M1 and M3 on day 0. However, it was observed that the M3‐derived product could retain its volatile profile better than the M1‐derived product by day 90. M3 was compared with freeze‐drying in the second experiment. Freeze‐dried truffles showed an overall higher relative percentage of volatiles than the M3‐derived product on day 0. However, by day 90, some volatile changes occurred in the freeze‐dried truffles but not in the M3‐derived product. The findings indicate that while freeze‐drying could adequately conserve truffle volatiles, the encapsulation of volatile compounds in β‐cyclodextrin could improve the volatile stability of truffle products and allow for longer storage times. Microbes were found in all encapsulated truffle products and freeze‐dried truffles on days 0 and 90, suggesting the need to explore the possibility of incorporating a decontamination step in the process prior to either encapsulation or freeze‐drying. Practical Application: A technique to capture and stabilize compounds responsible for truffle aroma by encapsulation using β‐cyclodextrin was developed and compared with freeze‐drying in this study. The overall finding suggests that while freeze‐drying of truffle could sufficiently preserve volatiles, encapsulating truffle volatiles with β‐cyclodextrin may improve its stability, extending its shelf life, which can be applied in the development of a natural truffle ingredient that can be applied in food product development.